Use of extratransference interpretation in psychoanalytic psychotherapy - Jojić Boris R. (Vojnosanitetski Pregled)
Background. In psychoanalytic psychotherapy, the transference analysis takes the central position of the work. The work in the extratransference sphere and experience in a professional practice with extratransference interventions have not been reported much in the literature. Extratransference sphere includes less transferring relation to a psychotherapist, transference to other objects, or may refer to the external reality rather than the psychic reality or fantasy. Case report. We pointed out extratransference interventions. We demonstrated an application of a genetic interpretation and reconstruction, too, which could restore and establish the connections between the past and the present, in order to understand the influences of the current reality and the past, and helping us, further, to resolve the infantile conflicts. Conclusion. Interpretation of extratransference situations takes an important part of an analytical work and it is an essential category of the interpretation. Analytic understanding should include transference and extratransference spheres, fantasy and reality, past and present. Working with neurotic patterns and character resistance needs an optimal choice of intervention in the given moment of the analytic process. Extratransference interventions are an essential category of intervention, irreplaceable for its effectiveness in the analytic process.